STUDY ON GAMOW-TELLER TRANSITION STRENGTHS IN A = 26 ISOBARS USING CHARGE EXCHANGE REACTION - NGUYEN , TUAN KHAI; TRAN , DUC THIEP; Y. FUJITA; T. ADACHI (Nuclear Science and Technology, 2011)
Isospin is a good quantum number to study isospin symmetry in isobars under the assumption that the nuclear interaction is charge symmetric. For A = 26 isobar triplet this symmetry is expected for the Tz = ±1 → 0 isobaric analogous transitions in , where Tz is the z component of isospin T and is defined by Tz = (N – Z) / 2. The isospin symmetric Tz = -1 → 0 Gamow-Teller (GT) transitions can be determined in the 26Si β decay. Assuming this symmetry it is possible to study the GT transition strengths for high excited states in 26Al induced by the (3He, t) charge-exchange (CE) reaction at intermediate energies (> 100 MeV/nucleon) and at forward scattering angles including 0o, where Tz = +1 → 0 GT transitions from the Jπ = 0+ ground state of 26Mg to the Jπ = 1+ excited states in 26Al were extended to the excitation energy (Ex) of 9 MeV.